Study on Genotypic Response and Correlation Analysis of the Yield and Yield Attributing Traits of Different Barley (Hordeum Vulgare) Genotypes - Vitrakoti, Deepak; Aryal, Sheetal; Rasaily, Santosh; Ojha, Bishnu Raj; Kharel, Raju; Sapkota, Manoj (International Journal of Applied Sciences and Biotechnology, 2017)
Barley, being a tremendous opportunities crop, we are far back regarding study, research and utilization. An experiment was conducted 2014-2015 to evaluate the barley genotypes for their yield attributing traits and correlation and causation. Eleven yield contributing traits viz., days to booting, heading and flowering; peduncle length, spike length, plant height, flag leaf area, flag leaf-1 area, thousand grain weight, biological weight and yield per hectare were recorded. High significant variation among genotypes was found for traits under study. Genotypes SBYT3-13#1115 (1960 kg), 14-SB-NAK-MR#17 (1760 kg) and AM POP#26 (1660 kg) were found to be superior for their per se performance based on grain yield per hectare, yield attributing and other quantitative traits. Thousand grains weight (0.333) had positively highest significant correlation with grain yield per hectare followed by spike length (0.310). Grain yield per hectare showed negative highly significant correlation with days to flowering (-0.796) followed by days to heading (-0.761) and days to booting (-0.663). Peduncle length (0.229), plant height (0.226), biological weight (0.181) and flag leaf area (0.032) were positively correlated with grain yield per hectare while flag leaf-1 area(-0.029) was negatively correlated. Thus, selection for genotypes with higher thousand grain weight and spike length accommodating earlier days to flowering, heading and booting is a prerequisite for attaining improvement in grain yield per hectare.Int J Appl Sci Biotechnol, Vol 4(4): 529-536